POLA KOMUNIKASI COFFEESHOP BLOGGER DALAM MEMBENTUK PERSONAL BRANDING DI INSTAGRAM - Khalida Azki Maudina; Hanny Hafiar; Centurion Chandratama Priyatna (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2022)
The growing number of coffee shops in Indonesia has made many food bloggers chose to make contents about coffee shop on their Instagram or known as coffee shop bloggers. This research is a phenomenology study with qualitative data with a purpose to answer questions about meaning of the profession as a coffee shop blogger; the motive of making coffee shop as the main content on Instagram; communication patterns in forming personal branding as a coffee shop blogger. This research applies phenomenological method and constructvism paradigm. Data collection techniques used are semitructured interviews, observation, literature studies, and online searches, with key informant collection techniques by purposive sampling. The validity technique uses data triangulation and observation. The results of this study indicate that; profession as a coffee shop blogger is interpreted as a means to generate income, to deepen knowledge, self-actualization, and to spread goodness, the motives in choosing coffee shop as the main content on Instagram are devided into two categories, which are the motives that oriented towards the past (because-motives and future oriented motives (in-order-to-motives); pattern of communication in building personal branding as a coffee shop blogger is divided into communication pattern when initially interested in becoming a coffee shop blogger and communication pattern after becoming a coffee shop blogger. Suggestions that can be given from this research are coffee shop bloggers should be more consistent in making content related to coffee shop and also writing captions that are informative in every posts. Coffee shops are expected to understand more about the benefits of using coffee shop blogger as new media tools for marketing activities.